Biting Midges of the Genus Culicoides in South Carolina Zoos - Nelder, Mark P. (University of Wisconsin Library, 2010)
Biting midges of the genus Culicoides (Diptera: Ceratopogonidae) were collected during the summer of 2007 at the Greenville and Riverbanks Zoos in South Carolina with Centers for Disease Control and Prevention (CDC) traps equipped with ultraviolet or incandescent lights and baited with carbon dioxide. Sixteen species of Culicoides were collected, four of which represented more than 80%. They were Culicoides guttipennis (Coquillett), Culicoides mulrenanni Beck, Culicoides obsoletus (Meigen), and Culicoides sanguisuga (Coquillett). C. guttipennis was found on a dead colobus monkey and a dead golden-headed lion tamarin; Culicoides husseyi Wirth & Blanton was collected from an unidentified, abandoned bird's nest. Ultraviolet light-equipped traps captured significantly more Culicoides specimens than traps with incandescent light. Half of the collected species previously have been associated with vertebrate pathogens, indicating a potential risk to captive animals.